Evaporation from seasonally frozen bare and vegetated ground at various groundwater table depths in the Ordos Basin, Northwest China. Issue 9 (21st February 2019) - Zhang, Zaiyong; Wang, Wenke; Gong, Chengcheng; Wang, Zhoufeng; Duan, Lei; Yeh, Tian‐chyi Jim; Yu, Peiyuan
Abstract: In cold climates, the process of freezing–thawing significantly affects the ground surface heat balance and water balance. To better understand the mechanism of evaporation from seasonally frozen soils, we performed field experiments at different water table depths on vegetated and bare ground in a semiarid region in China. Soil moisture and temperature, air temperature, precipitation, and water table depths were measured over a 5‐month period (November 1, 2016, to March 14, 2017). The evaporation, which was calculated by a mass balance method, was high in the periods of thawing and low in the periods of freezing. Increased water table depth in the freezing period led to high soil moisture in the upper soil layer, whereas lower initial groundwater levels during freezing–thawing decreased the cumulative evaporation. The extent of evaporation from the bare ground was the same in summer as in winter. These results indicate that a noteworthy amount of evaporation from the bare ground is present during freezing–thawing. Finally, the roots of Salix psammophila could increase the soil temperature. This study presents an insight into the joint effects of soil moisture, temperature, ground vegetation, and water table depths on the evaporation from seasonally frozen soils. Furthermore, it also has important implications for water management in seasonally frozen areas.